2006
DOI: 10.1111/j.1365-2133.2006.07417.x
|View full text |Cite
|
Sign up to set email alerts
|

Schnitzler syndrome associated with systemic marginal zone B-cell lymphoma

Abstract: Schnitzler syndrome is a rare condition defined by chronic urticaria and monoclonal IgM gammopathy. Malignant evolution to Waldenström disease (WD) has been reported in several cases. We report a 49-year-old man who developed a marginal zone B-cell lymphoma (MZL) 3 years after the beginning of Schnitzler syndrome. This is the first report of MZL in association with Schnitzler syndrome. IgM gammopathy is a clue for the diagnosis of Schnitzler syndrome. This condition needs to be closely monitored; it can preced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 15 publications
0
23
0
1
Order By: Relevance
“…To our knowledge, the association between Schnitzler syndrome and marginal zone lymphoma (splenic or nodal) has been reported only once previously. 19 We did not identify any specific clinical characteristic or histopathologic pattern that was associated with development of a lymphoproliferative disorder. In our study, the average time to development of malignancy was 7.6 years from onset of signs and symptoms of Schnitzler syndrome.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…To our knowledge, the association between Schnitzler syndrome and marginal zone lymphoma (splenic or nodal) has been reported only once previously. 19 We did not identify any specific clinical characteristic or histopathologic pattern that was associated with development of a lymphoproliferative disorder. In our study, the average time to development of malignancy was 7.6 years from onset of signs and symptoms of Schnitzler syndrome.…”
Section: Discussionmentioning
confidence: 85%
“…Schnitzler syndrome has been associated with other lymphoproliferative disorders, including lymphoplasmacytic lymphoma, multiple myeloma, and marginal zone B-cell lymphoma, but these associations typically have been infrequent. 1,3,19 In addition to Waldenstr€ om macroglobulinemia, patients in our cohort had lymphoplasmacytic lymphoma, chronic lymphocytic leukemia, multiple myeloma, splenic marginal zone lymphoma, and marginal zone B-cell lymphoma. To our knowledge, the association between Schnitzler syndrome and marginal zone lymphoma (splenic or nodal) has been reported only once previously.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently, development of an IgM-secreting marginal zone B-cell lymphoma in a patient with Schnitzler syndrome has been described for the first time. 8 Regular follow-ups are, therefore, necessary. Lipsker et al 7 suggested an initial examination of bone marrow, immunoelectrophoresis of serum and urinary proteins, and determination of immunoglobulin subtypes, with biannual repetitions of the two latter parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The association of Schnitzler syndrome with various lymphoproliferative disorders such as marginal zone B-cell lymphoma, IgM myeloma, and Waldenström macroglobulinemia (WM) has been reported. [2][3][4][5] However, the best therapeutic strategy for such complicated cases has not been established. This report presents a case of B-cell lymphoma developing in a patient with Schnitzler syndrome, who was treated by combination therapy of rituximab and radiotherapy.…”
mentioning
confidence: 99%